1999
DOI: 10.1001/archinte.159.17.2077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Web-Based Clinical Information System on Cisapride Drug Interactions and Patient Safety

Abstract: An automated system running as a safety net can be an efficient method of detecting contraindicated drug combinations and serves an important role in the avoidance of potentially serious adverse drug events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In 1 study of computer-based alerts associated with cisapride, these alerts reduced the rate of potentially dangerous drug combinations by 66%. 74 More sophisticated computer algorithms may ultimately allow adjustments for risk amplifiers to stratify the arrhythmic risk for individual patients and to guide clinicians away from the use of high-risk agents and toward the use of lower-risk alternatives when available. Some of the variables that might be used in this risk stratification approach include patient age, gender, body mass index, electrolyte abnormalities, concomitant drugs, and assessments of cardiac, renal, and hepatic function.…”
Section: Heist and Ruskinmentioning
confidence: 99%
“…In 1 study of computer-based alerts associated with cisapride, these alerts reduced the rate of potentially dangerous drug combinations by 66%. 74 More sophisticated computer algorithms may ultimately allow adjustments for risk amplifiers to stratify the arrhythmic risk for individual patients and to guide clinicians away from the use of high-risk agents and toward the use of lower-risk alternatives when available. Some of the variables that might be used in this risk stratification approach include patient age, gender, body mass index, electrolyte abnormalities, concomitant drugs, and assessments of cardiac, renal, and hepatic function.…”
Section: Heist and Ruskinmentioning
confidence: 99%
“…A previous study documented a 66% reduction in the rate of dangerous drug combinations associated with cisapride when computer-generated alerts to the prescribing physician were used (Figure 9). 36 In the future, increasing sophistication of computer-based prescription systems may be expected to incorporate a wide range of patient-specific risk factors, such as age, gender, weight, coadministration of other agents, renal and hepatic function, and, possibly, genetic information, to assist the prescriber in evaluating and minimizing arrhythmic risk for individual patients. 37 For the present, a thorough understanding of the causes and prevention strategies for druginduced arrhythmia, combined with available computer and web-based prescribing algorithms, serves as the best protection against very rare but potentially life-threatening ventricular arrhythmias related to commonly used drugs.…”
Section: Computer-assisted Approachesmentioning
confidence: 99%
“…Prescribing of dangerous drug combinations declined by 66% after the system was implemented (P Ͻ0.001). 36 …”
Section: Figurementioning
confidence: 99%
“…The effects of sitagliptin safety alert were also analyzed using Japanese hospital data (Sato et al, 2012(Sato et al, , 2013. Example of cisapride showed that safety letters were not effective, whereas the computerized system was effective in changing the prescribing behaviors (McMullin et al, 1999;Smalley et al, 2000). However, this study showed that both safety letters and computerized system were effective for reducing methylphenidate use in children aged five and under.…”
Section: Discussionmentioning
confidence: 99%